2018
DOI: 10.1155/2018/1978639
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytosis as a Marker for Postoperative Complications in Colorectal Surgery

Abstract: Background Blood platelet measurement is a widely available and inexpensive test that is performed routinely. Platelets are thought to act by inducing inflammation and play a role in clotting and antimicrobial defence. A postoperative rise in the platelet count (thrombocytosis) is often dismissed as an incidental finding, but there is growing evidence to suggest that it may act as an indicator to underlying pathology. It correlates with significant pyogenic infections as well as multiple malignancies. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…Our findings of increased inflammation caused by elevated hsCRP, WBC and IL-6 with a differentiated response depending on mode of surgery are consistent with other trials in endometrial cancer surgery and in colorectal surgery, as is likewise the significant thrombocytosis we found, independent of the mode of surgery (Pilka, et al 2016, Zawadzki, et al 2017, Mohamud, et al 2018).…”
Section: Cortisolsupporting
confidence: 92%
“…Our findings of increased inflammation caused by elevated hsCRP, WBC and IL-6 with a differentiated response depending on mode of surgery are consistent with other trials in endometrial cancer surgery and in colorectal surgery, as is likewise the significant thrombocytosis we found, independent of the mode of surgery (Pilka, et al 2016, Zawadzki, et al 2017, Mohamud, et al 2018).…”
Section: Cortisolsupporting
confidence: 92%
“…Even the thrombocytes showed a similar pattern, although Pilka could not observe the significant thrombocytosis independent of the mode of surgery that we noticed one week postoperatively because in Pilka's study the collection of blood samples was limited to only five days after surgery. www.nature.com/scientificreports www.nature.com/scientificreports/ The reactive or secondary thrombocytosis that appears after elective colorectal surgery usually reaches a peak level at a median of eight days after surgery 20 . Thus, our results might indicate that the mechanisms for developing postoperative thrombocytosis are not dependent on mode of surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found several other RFs found more frequently in deceased patients, with differences sometimes reaching statistical significance: thrombocytosis, COPD, hepatic or digestive conditions, induction chemotherapy, ASA classes III and IV and the presence of suppurations, especially TB. Thrombocytosis (a platelet count above 40 x 10 4 /mL) was defined as a RF for increased morbidity and mortality in oncological surgery for colorectal (12), gynaecological (in association with leucocytosis) ( 13) and pulmonary cancers (14). Kim et al (14) found that preoperative thrombocytosis increases the mortality 2.47-fold in non-small-cell lung cancer (NSCLC) patients.…”
Section: Resultsmentioning
confidence: 99%